Body shape dissatisfaction is a 'normative discontent' in a young-adult Nigerian population: A study of prevalence and effects on health-related quality of life - Chukwunonso E.C.C. Ejike (Springer, 2015)
This study investigates the prevalence of weight misperception, weight preference, and body shape dissatisfaction (BSD) among young-adult Nigerians and assesses the impact of these factors on population quality-of-life (QOL). Relevant anthropometric data were collected according to internationally accepted protocols. Weight perception, weight preference, and BSD were measured using Stunkard silhouettes, while QOL was determined by subjective self-reporting. The results show that 26.7% of the population (18.8% for males and 34.5% for females) misperceived their weight. Among overweight participants, 56.6% (males) and 38.3% (females) thought they were thinner, while 11.5% (males) and 43.3% (females) thought they were heavier. Thin and obese males misperceived their weights more than their female counterparts. BSD was found in 62% of the population (52% for males and 71% for females) and was highest among obese participants (91.9%) and lowest among normal-weight participants (58.2%), irrespective of sex. In participants with BSD, QOL was worse in thin and normal-weight respondents who preferred to be heavier and in overweight respondents who preferred to be thinner. The high prevalence of weight misperception may lead to inappropriate weight loss habits, while BSD, a normative discontent in this population, negatively impacts subject QOL.